THERMAL SHRINKAGE AND YIELD STRENGTH OF GELLED WAXY CRUDE OIL - AMAR SINGH, JASPREET KAUR (2013)
The concern for flow assurance of reservoir fluids to the surface and subsequently delivering it to the appropriate markets becomes very critical to justify project economics and to meet the ever growing demand for petroleum products. Due to emergency or maintenances purpose, the production systems cumu ue >hul <taw. b enough to form waxy crude oil gels in the subsea pipelines which can completely interrupt further production. Moreover, the formation and deposition of waxy crude oil which occurs at the inner wall ofthe pipeline will reduce the internal diameter and cause blockage. Therefore, waxy crude oils create many flow assurance issues inherently linked to them and understanding of the effect of relevant factors and phenomena are ofgreat practical importance.